Technology-Enhanced Vs. Traditional Approaches To Pediatric Nutrition Education: A Comparative Analysis - Nurwati, Yuni (Journal of Engineering Science and Technology Management (JES-TM), 2025)
The digital transformation in education has introduced innovative approaches to paediatric nutrition education, offering alternatives to traditional methods. This comparative analysis examined the effectiveness of technology-enhanced versus traditional approaches in improving nutritional knowledge and behaviour among Indonesian children and adolescents. The aimed of this review was to systematically compare the effectiveness of technology-enhanced and traditional approaches to paediatric nutrition education based on primary research studies conducted in Indonesia. This review analyzed ten primary research studies conducted in Indonesia between 2015-2025, examining various educational intervention including digital media (videos, mobile applications, social media), interactive games, and traditional methods (leaflets, face-to-face counselling) across different paediatric populations. Technology-enhanced interventions demonstrated superior effectiveness compared to traditional methods. Digital interventions showed knowledge improvement rates ranging from 19.5% to 73.3%, while traditional methods achieved 8.2% to 12.6% improvement. Video-based education proved most effective (mean improvement: 27.39 points), followed by mobile applications (68% to 87.3% correct response) and social media platforms. In conclusion, technology-enhanced approaches to paediatric nutrition education significantly outperformed traditional methods in improving nutritional knowledge and attitudes among Indonesian children and adolescents, with video-based interventions showing the highest efficacy.